Assessing the Value of a Societal-Level Sustainability Index for Macromarketing Research. (March 2016) - Simkins, Travis Jody; Peterson, Mark
As the Internet makes secondary data increasingly more accessible and less costly to obtain, the need for methods to evaluate the reliability and validity of such data has grown accordingly. In efforts to harness the surge of data at the country level, researchers have created indexes to more efficiently track the performance of societies on a variety of dimensions. Large-scale global indexes like the Sustainable Society Index (SSI), published biannually since 2006 by the Sustainable Society Foundation, have the potential to provide valuable insights into important issues related to macromarketing, sustainability, and quality of life. The primary purpose of this article is to assess the value of a societal-level index for macromarketing research. By evaluating the reliability, internal validity and external validity of a societal-level index, such as the SSI, researchers will be better informed about the importance of such an index, but will also understand how the protocol used in this study can be applied to other indexes. In order to gauge the external validity of the SSI, the study also evaluates and utilizes three other established secondary data sources in conjunction with the SSI. These include: (1) the Legatum Prosperity Index; (2) Transparency International's Corruption Perceptions Index; and (3) the Euromoney Country Risk Index.